FINITE ELEMENT ANALYSIS OF CONCRETE BEAM WITH POLYVINYL ALCOHOL FIBER - Mohd Saidi, Mohd Farid (Universiti Teknologi Petronas, 2007)
This study presents the results of the computational modeling and analysis for evaluating the effect of Polyvinyl Alcohol Fiber (PV A) as an internal strengthening material to concrete beam. A concentrated load was applied to several two pin simply supported beam model. A finite element method was used. The results show that the internal PV A strengthening was able to increase the structural strength capacity of the beam. From the stress contours, the failure mechanism observed show that the strengthened concrete beam fail in the tension zone. The possible failure of the strengthened concrete maybe due to crushing of concrete at the bottom of beam. This type of failure generally, occurs when the stress exceed the tensile strength of cement mortar. Therefore, structural strength of this concrete is highly depending of the PVA.